2004
DOI: 10.5688/aj680103
|View full text |Cite
|
Sign up to set email alerts
|

A Management Skills Course for Pharmacy Students

Abstract: Objective. This paper describes the planning and implementation of a 3-credit pharmacy management skills course taught to third-year Doctor of Pharmacy students at Shenandoah University. The purpose of this course was to help pharmacy students to develop and improve their management skills. Design. The curriculum for the course was based on a 5-step social learning theory model that included self-awareness, skill learning, skill analysis, skill practice, and skill application. A diverse number of methods were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 16 publications
1
41
0
5
Order By: Relevance
“…Professionalism and bioethical principles for pharmacy students Pharmacy Education 20(1) 158 -167 160 Studies have considered students' ethical frames of reference (Latif, 2003;Latif, 2004;Cooper et al, 2007;Gallagher, 2011;Okoye et al, 2017;Hanna et al, 2017), including studies that investigated the use of case scenarios to elicit students' responses about how they deal with ethical dilemmas (Donaldson et al, 2010;Frunză, 2011;Schlesselman, 2014;Lindsey & Olin, 2014;Smith & Dinkins, 2015;Henning et al, 2016). To the authors' knowledge, no such studies have been conducted among pharmacy students in Nigeria.…”
Section: Okoro and Biambomentioning
confidence: 99%
“…Professionalism and bioethical principles for pharmacy students Pharmacy Education 20(1) 158 -167 160 Studies have considered students' ethical frames of reference (Latif, 2003;Latif, 2004;Cooper et al, 2007;Gallagher, 2011;Okoye et al, 2017;Hanna et al, 2017), including studies that investigated the use of case scenarios to elicit students' responses about how they deal with ethical dilemmas (Donaldson et al, 2010;Frunză, 2011;Schlesselman, 2014;Lindsey & Olin, 2014;Smith & Dinkins, 2015;Henning et al, 2016). To the authors' knowledge, no such studies have been conducted among pharmacy students in Nigeria.…”
Section: Okoro and Biambomentioning
confidence: 99%
“…De même, il existe relativement peu de publications sur le sujet. Latif a décrit en 2004 un cours de gestion pharmaceutique en troisième année du programme de premier cycle de doctorat professionnel [35] . Calomo a rapporté en 2006 une expérience dans un cours similaire destiné aux étudiants formés pour l'exercice en pratique communautaire [36] .…”
Section: Cela A-t-il éTé Fait Réelleunclassified
“…Plaza et al found that self-efficacy was useful in evaluating curricular change and had potential benefits to experiential education. 10 Other examples of self-efficacy use or consideration within pharmacy education have included management course redesign 11 , tobacco cessation course development 12 , clinical nutrition course implementation 13 , and its application within a goal-efficacy framework regarding pharmacy student success.…”
Section: Trait: Self-efficacymentioning
confidence: 99%